2010
DOI: 10.1097/wno.0b013e3181f7f833
|View full text |Cite
|
Sign up to set email alerts
|

Oral Resveratrol Reduces Neuronal Damage in a Model of Multiple Sclerosis

Abstract: Background Neuronal loss in multiple sclerosis (MS) and its animal model, experimental autoimmune encephalomyelitis (EAE), correlates with permanent neurological dysfunction. Current MS therapies have limited ability to prevent neuronal damage. Methods We examined whether oral therapy with SRT501, a pharmaceutical-grade formulation of resveratrol, reduces neuronal loss during relapsing/remitting EAE. Resveratrol activates SIRT1, an NAD+-dependent deacetylase that promotes mitochondrial function. Results Or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
151
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(163 citation statements)
references
References 29 publications
9
151
1
2
Order By: Relevance
“…We also studied SIRT1 (Haigis and Guarente, 2006;Shindler et al, 2010;Rahman and Islam, 2011), a NAD-dependent protein deacetylase, because it has emerged as a regulator of mammalian transcription in the response to cellular metabolic stress with neuroprotective effects (Gao et al, 2010). We found that SIRT1 expressing cells increased in the spinal cord in transplanted mice with EAE compared to untransplanted normal mouse tissue and that the doxycycline treated transplanted mice with EAE had higher numbers of SIRT1 expressing cells than transplanted EAE mice that did not receive doxycycline.…”
Section: Discussionmentioning
confidence: 92%
“…We also studied SIRT1 (Haigis and Guarente, 2006;Shindler et al, 2010;Rahman and Islam, 2011), a NAD-dependent protein deacetylase, because it has emerged as a regulator of mammalian transcription in the response to cellular metabolic stress with neuroprotective effects (Gao et al, 2010). We found that SIRT1 expressing cells increased in the spinal cord in transplanted mice with EAE compared to untransplanted normal mouse tissue and that the doxycycline treated transplanted mice with EAE had higher numbers of SIRT1 expressing cells than transplanted EAE mice that did not receive doxycycline.…”
Section: Discussionmentioning
confidence: 92%
“…With the ongoing degeneration that is associated with progressive MS and the presence of OS at sites of degeneration, 2,8,9,79,80 determining the utility of anti-oxidant therapies to protect neural tissue or promote repair is a major research gap. In this review, we found that only EGCG, 37,38 vitamin E, 44,53 reservatrol, 33,35 and ALA 66,69,70 promoted remyelination and/ or protected neurons from inflammatory-mediated damage (in animal models). Resveratrol consistently provided neuroprotection in EAE, though this was independent of any anti-inflammatory benefits.…”
Section: Optimal Outcomes To Assess the Benefits Of Antioxidantsmentioning
confidence: 99%
“…43 It is known to have poor bioavailability, so most studies administer SRT501, a pharmaceutical formulation of resveratrol that has enhanced systemic absorption. 33,43 In four studies reviewed (all in animal models), both resveratrol and SRT501 consistently decreased EAE severity, [33][34][35][36] which coincided with reduced optic nerve damage and prevention of retinal ganglion cell loss. 33,35 Resveratrol did not alter the levels of infiltrating immune cells into the spinal cord of EAE animals, suggesting it functions through a neuroprotective mechanism; [33][34][35] though one group reported decreased levels of peripheral pro-inflammatory cytokines.…”
Section: Polyphenolsmentioning
confidence: 99%
See 2 more Smart Citations